MANAJEMEN KESISWAAN DALAM PENINGKATAN POTENSI SISWA MELALUI EKSTRAKULIKULER SMA A. WAHID HASYIM TEBUIRENG JOMBANG - Irmanisa; Lukman Hakim (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
Student management is an arrangement or regulation of all activities related to students from entry to graduation. Student management aims to increase the effectiveness and efficiency of school services so that the knowledge, skills and attitudes of students develop through the channeling of aspirations, hopes and fulfillment of needs. One of the student management services is extracurricular activities, namely curricular activities carried out by students outside of class hours. This activity aims to develop and actualize the potential of students optimally, strengthen the personality of students to avoid negative influences, and prepare students to become citizens who are noble, democratic, respect human rights in order to create civil society. This research includes field research using a qualitative approach. In data collection. The author uses interview, observation, and documentary methods, and data analysis techniques use triangulation techniques, diligent and objective observation, and peer checking through discussion. The results showed: (1) Student Management at SMA A. Wahid Hasyim Tebuireng Jombang was carried out as much as possible to facilitate and serve students so that they could produce students who were in accordance with educational goals and in accordance with what was expected by their environment; 2. Developing the potential of students is carried out by providing space for potential development and facilities for students to develop hard-skills and soft-skills through extracurricular activities: 3. Extracurricular activities are integrated with the curriculum of the education unit and are managed specifically by the student affairs department in collaboration with curriculum field. Planning begins with mapping students' abilities and interests, recruiting new extracurricular members, compiling a program for one semester; implementation includes routine training, participation in competitions, and documentation of competition results; Supervision is carried out in the absence of members and trainers, monthly evaluations, reports and assessments every semester